Low coral mortality during the most intense bleaching event ever recorded in subtropical Southwestern Atlantic reefs - Banha, T. N. S.; Capel, K. C. C.; Kitahara, M. V.; Francini-Filho, R. B.; Francini, C. L. B.; Sumida, P. Y. G.; Mies, M. (Coral reefs, 2020)
Coral reefs globally are threatened by climate change, but reef assemblages at high latitudes may serve as refugia. Marginal coral communities located in the subtropical Southwestern Atlantic are poorly studied, but were subject to an unprecedented heatwave and associated coral bleaching in 2019. Record values of 18.5 and 20.5 °C-weeks were registered for coastal and insular sites, which are the highest ever documented for a reef in the South Atlantic. As a consequence, approximately 80% and 20% of the population of the reef-building coral Mussismilia hispida (1116 colonies surveyed) underwent bleaching in coastal and insular sites, respectively. However, mortality (2%) was far lower than for episodes of similar magnitude in other regions, particularly in the Indo-Pacific. Therefore, the subtropical Southwestern Atlantic MCC displayed low mortality and remarkable tolerance when exposed to the most intense bleaching episode ever recorded for the region, reinforcing its potential as a refugium.